2021
DOI: 10.1111/vsu.13584
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a hands‐on veterinary surgical training course from a traditionally taught laboratory to a remotely taught laboratory during a global pandemic

Abstract: Objective: The goal of this study was to evaluate and report details of a remotely taught surgical laboratory. Study design: Observational. Sample population: Second-year veterinary students (n = 143) enrolled in a surgical laboratory; 9 weeks were taught traditionally, and 6 weeks were taught remotely. Methods: Because of the global pandemic, remote laboratories were developed and delivered. Students performed surgical procedures in model organs remotely while being observed by and receiving feedback from ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In addition, some models successfully reproduce the organs with pre-existing pathology such as cerebral aneurysms (20,21) and basilar invagination (22). Studies assessing the use of 3D printed models for surgical training have generally supported their benefits for surgical education (23) and recently in the field of veterinary medicine, Kelly reported the use of 3D models to teach students surgical anatomy remotely (24). Several additional small studies assessing remote training for surgical skills have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some models successfully reproduce the organs with pre-existing pathology such as cerebral aneurysms (20,21) and basilar invagination (22). Studies assessing the use of 3D printed models for surgical training have generally supported their benefits for surgical education (23) and recently in the field of veterinary medicine, Kelly reported the use of 3D models to teach students surgical anatomy remotely (24). Several additional small studies assessing remote training for surgical skills have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a suture board model is associated with the limitations of using a model to reflect a skill that is generally performed in live patients; however, models are generally widely accepted for the use of evaluating intraoperative skills. 23,24 Future studies performed in clinical OR environments with live patients are required to confirm the results of this model-based study.In conclusion, answering questions will decrease suturing speed in comparison with listening to favorable music. This distraction appears to have the greatest effect on those surgeons with minimal experience and may be more pronounced in less experienced male veterinarians and veterinary students.…”
Section: Discussionmentioning
confidence: 76%
“…This is due to societal and student demand for humane education, improved animal welfare and good-quality learning. [1][2][3][4] In surgical training, such non-animal didactic methods are of increasing importance as viable alternatives to the traditional use of cadavers, which have many disadvantages (such as problems with sourcing, maintenance and ongoing autolysis). 5,6 In particular, the inevitable organ degradation due to cadaver autolysis makes it impossible for a cadaver to mimic a live animal for some surgical procedures, thus delaying effective skill acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] These issues make it all the more important to find materials that can be used to create suitable alternatives to cadavers for surgical practical classes. 2,3 In Brazil, the teaching of cystotomy and nephrectomy procedures is considered to be an essential element of veterinary training because urinary tract disease is very common in small animal practice. For cats in particular, surgical management is needed for many common lower urinary tract diseases 15 (e.g.…”
Section: Introductionmentioning
confidence: 99%